O estado da arte das pesquisas brasileiras sobre o letramento estatístico e probabilístico - Paim, Sandra Aparecida de Oliveira Coelho (Universidade Federal de São Carlos, 2019)
Among the thematic studies of GEPLAM (Mathematics Classes Study and Planning Group), based on the Sorocaba campus of the Federal University of São Carlos (UFSCar), we highlight Statistical and Probabilistic Literacy from Iddo Gal's perspective, theoretical contributions of completed. From the appropriation of a portion of Gal's academic production (2002, 2005, 2012) by GEPLAM members in their studies, we sought to investigate how this theoretical contribution has contributed to the development of theses and dissertations in the national scenario, more specifically , What is the incidence of statistical and probabilistic literacy elements addressed in Brazilian theses and dissertations? The objective was to present a State of the Art, adopting a qualitative bibliographical methodology, exposing a descriptive and qualitative analysis of the data related to statistical and / or probabilistic literacy, present in Brazilian theses and dissertations, giving continuity to the survey of the academic productions made by Santos 2015), in the period from 2013 to 2018, developed in contexts of Elementary School, High School, initial and / or continuous training of teachers teaching Mathematics. Three categories of analysis were created: the academic productions that used the Probabilistic Letters, searching for the cognitive and disposition components; those who used the Statistical Literacy, but looking for the elements of knowledge and disposition, and those that used the Statistical and Probabilistic Literacy articulating the two previous ones. It could be noticed in the analyzed works, although they used different methodologies and varied "subjects" proposed to research because the probabilistic and / or statistical literacy is still not being reached.
The state of the art of brazilian research on statistical and probabilistic literacy
Keywords: Estado da Arte; Letramento Probabilístico; Letramento Estatístico; State of the Art; Probabilistic Literacy; Statistical Literacy; CIENCIAS EXATAS E DA TERRA::MATEMATICA